Recent progress in Ga2O3 power devices - Higashiwaki, Masataka; Sasaki, Kohei; Murakami, Hisashi; Kumagai, Yoshinao; Koukitu, Akinori; Kuramata, Akito; Masui, Takekazu; Yamakoshi, Shigenobu (Semiconductor science and technology, 2016)
This is a review article on the current status and future prospects of the research and development on gallium oxide (Ga2O3) power devices. Ga2O3 possesses excellent material properties, in particular for power device applications. It is also attractive from an industrial viewpoint since large-size, high-quality wafers can be manufactured from a single-crystal bulk synthesized by melt-growth methods. These two features have drawn much attention to Ga2O3 as a new wide bandgap semiconductor following SiC and GaN. In this review, we describe the recent progress in the research and development on fundamental technologies of Ga2O3 devices, covering single-crystal bulk and wafer production, homoepitaxial thin film growth by molecular beam epitaxy and halide vapor phase epitaxy, as well as device processing and characterization of metal-semiconductor field-effect transistors, metal-oxide-semiconductor field-effect transistors and Schottky barrier diodes.